The Effect of a Combination of Activated Carbon and Bentonite on Reducing COD, BOD, and TSS Levels in Tofu Industry Wastewater - Barita Aritonang; Ahmad Hafizullah Ritonga; Karnirius Harefa; Dicky Yuswardi Wiratma; herlina herlina (Jurnal FARMASIMED (JFM), 2025)
Wastewater produced from tofu manufacturing typically contains substantial amounts of organic substances and suspended particles. The concentrations of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solids (TSS) frequently surpass the permissible thresholds established in the Regulation of the Minister of Environment and Forestry (Permen LHK) No. P.16 of 2019. Such high levels of pollutants may degrade water quality and pose risks to both aquatic ecosystems and public health in nearby areas. This study investigates the efficiency of combining activated carbon and bentonite, in both raw and activated forms, for reducing BOD, COD, and TSS concentrations in wastewater originating from tofu industries. The BOD test was performed using a five-day incubation at 24 °C, COD was analysed via the closed reflux method, and TSS was quantified using the gravimetric approach. Adsorbent characteristics were examined in accordance with the Indonesian National Standard (SNI), supported by functional group analysis using Fourier Transform Infrared (FT-IR) spectroscopy and morphological observation with Scanning Electron Microscopy (SEM). The results demonstrated that activation enhanced pore development and improved the adsorption capability of both materials. The combined activated carbon and bentonite effectively decreased BOD from 3,600 mg/L to 140 mg/L, COD from 1,500 mg/L to 185 mg/L, and TSS from 320 mg/L to 270 mg/L. All treated parameters met the regulatory quality standards, indicating that the activated mixture of these adsorbents provides an efficient and environmentally sound method for treating tofu processing wastewater.